2019
DOI: 10.1007/s40200-019-00414-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mobile learning (application) on self-care behaviors and blood glucose of type 2 diabetic patients

Abstract: Purpose More than 70% of the health expenditure is related to chronic diseases. Therefore, an efficient managerial program can markedly reduce medical and administrative costs and benefit both patients and service providers. The use of mobile technologies can be very helpful in this regard. This study was conducted to determine the effect of mobile learning (application) on self-care behaviors and blood glucose control of type 2 diabetic patients attending the Diabetes Clinic of Imam Khomeini Hospital Complex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
0
8
1
Order By: Relevance
“…In total, we included 27 papers analyzing 1646 patients in the intervention groups and 1241 in the control groups. Of the 27 papers, 7 were focused on T1DM (308 patients in the intervention groups and 129 patients in the control groups) [43][44][45][46][47][48][49], 12 were focused on T2DM (743 patients in the intervention groups and 645 patients in the control groups) [50][51][52][53][54][55][56][57][58][59][60][61], and 4 were focused on GDM (339 patients in the intervention groups and 343 patients in the control groups) [62][63][64][65]. The remaining 4 papers did not specify the type of DM they looked at or included a mix of DM types (256 patients in the intervention groups and 124 patients in the control groups) [66][67][68][69].…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, we included 27 papers analyzing 1646 patients in the intervention groups and 1241 in the control groups. Of the 27 papers, 7 were focused on T1DM (308 patients in the intervention groups and 129 patients in the control groups) [43][44][45][46][47][48][49], 12 were focused on T2DM (743 patients in the intervention groups and 645 patients in the control groups) [50][51][52][53][54][55][56][57][58][59][60][61], and 4 were focused on GDM (339 patients in the intervention groups and 343 patients in the control groups) [62][63][64][65]. The remaining 4 papers did not specify the type of DM they looked at or included a mix of DM types (256 patients in the intervention groups and 124 patients in the control groups) [66][67][68][69].…”
Section: Overviewmentioning
confidence: 99%
“…In total, 743 patients in intervention groups and 645 patients in control groups were investigated in the studies focused on T2DM. Eleven of the studies reported a decrease of HbA 1c within the app intervention groups, yielding a mean difference of -0.42% [50][51][52][54][55][56][57][58][59][60][61], but only 1 study reported a significant change of -1.1% (P<.001) [56]. The proportion changes when differences between intervention and control groups were considered.…”
Section: Hba 1cmentioning
confidence: 99%
See 3 more Smart Citations